2020
DOI: 10.1111/cas.14578
|View full text |Cite
|
Sign up to set email alerts
|

Functional diversity of cancer‐associated fibroblasts in modulating drug resistance

Abstract: Over the past few decades, advances in this field have demonstrated that the complexity of cancer is not only dependent on the intrinsic characteristics of tumor cells but also mainly determined by crosstalk between altered cancer cells and various components of the tumor microenvironment (TME). This complexity has become a considerable obstacle in discovering the specific mechanism(s) underlying treatment failure. Many various cell types are present within the TME, including fibroblasts and endothelial, adipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 83 publications
0
48
0
Order By: Relevance
“…The simultaneous high levels of these pro-inflammatory cytokines are significantly associated with a poor prognosis of patients with GC [ 75 ]. Studies have reported that CAFs are a heterogeneous cell population consisting of different cell subsets with different functions [ 76 , 77 , 78 ]. According to a report from Öhlund et al [ 79 ], there are two spatially and functionally distinct CAF populations, namely inflammatory CAFs (iCAFs) and myofibroblastic CAFs (myCAFs).…”
Section: Cell Types Engaged In Cancer-associated Inflammationmentioning
confidence: 99%
“…The simultaneous high levels of these pro-inflammatory cytokines are significantly associated with a poor prognosis of patients with GC [ 75 ]. Studies have reported that CAFs are a heterogeneous cell population consisting of different cell subsets with different functions [ 76 , 77 , 78 ]. According to a report from Öhlund et al [ 79 ], there are two spatially and functionally distinct CAF populations, namely inflammatory CAFs (iCAFs) and myofibroblastic CAFs (myCAFs).…”
Section: Cell Types Engaged In Cancer-associated Inflammationmentioning
confidence: 99%
“…The possibility of creating consistent 3D cell cultures at quantities suitable for HTS also opens the potential for tissue-relevant co-culture models. Recently, pro-inflammatory signaling by fibroblasts has moved into the focus of cancer treatment research for its contribution to cancer drug resistance 22 . We therefore created 3D dermal fibroblast cultures in our third workflow validation experiment to assess the release of the pro-inflammatory cytokine interleukin 6 (IL-6) following stimulation with bacteria wall segments (lipopolysaccharide, LPS) and compare the activation profile with 2D cultures.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that CAFs can also facilitate cancer progression by promoting tumor cell resistance to cytotoxic therapies [ 120 , 121 ]. Several studies have demonstrated that certain CAFs in human CRCs are also able to do so.…”
Section: Fibroblasts In Advanced Crc Progression and Metastasismentioning
confidence: 99%